2015
DOI: 10.1093/jac/dkv122
|View full text |Cite
|
Sign up to set email alerts
|

Serum and cellular ribavirin pharmacokinetic and concentration–effect analysis in HCV patients receiving sofosbuvir plus ribavirin

Abstract: RBV-MP concentrations in RBC at day 14 were related to anaemia and SVR. A therapeutic range was identified for RBV-MP in persons with HCV GT1 disease receiving 24 weeks of sofosbuvir plus ribavirin, suggesting a potential pharmacological basis for individualized ribavirin dosing in IFN-free regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 33 publications
5
22
0
Order By: Relevance
“…In combination with PEG, higher RBV concentrations are associated with a higher likelihood of SVR . This association has also been observed in interferon‐free regimens . Thus, reductions in RBV dose due to hemolytic anemia could potentially compromise SVR …”
Section: Itpa Genotype Groups With Number and Percentage Of Patients mentioning
confidence: 82%
See 2 more Smart Citations
“…In combination with PEG, higher RBV concentrations are associated with a higher likelihood of SVR . This association has also been observed in interferon‐free regimens . Thus, reductions in RBV dose due to hemolytic anemia could potentially compromise SVR …”
Section: Itpa Genotype Groups With Number and Percentage Of Patients mentioning
confidence: 82%
“…For the PAXgene ® sample, whole blood was drawn into PAXgene ® RNA tubes (Qiagen, Valencia, California) followed by immediate storage at –20°C followed by long‐term storage at –70°C. The sample was then diluted 1:50 in 1 mL of 70% methanol and stored at –70°C until bioanalytical processing …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the NIAID SPARE trial, Rower et al [46] , showed that ribavirin-monophosphate concentrations in red blood cells at day 14 were related to anaemia and SVR. A therapeutic range was identified for ribavirinmonophosphate in persons with HCV G1 disease receiving 24 wk of sofosbuvir plus ribavirin, suggesting a potential pharmacological basis for individualized ribavirin dosing in this interferon-free regimen.…”
Section: There Is Probably No More Place For Ribavirin Dose Adjustmenmentioning
confidence: 99%
“…Ribavirin (RBV; l‐ß‐D‐ribofuranosyl‐l,2,4‐triazole‐3‐carboxamide) is a purine nucleoside analog with broad‐spectrum antiviral activity against a variety of viruses (Fernandez et al ., ; Maag et al ., ; Lin et al ., ; K. Gupta et al ., ). In humans, oral ribavirin therapy is regarded as a major antiviral prescription to treat hepatitis C virus (HCV) infections, in combination with interferons (Maag et al ., ; Rower et al ., ). Ribavirin has various antiviral mechanisms such as the inhibition of inosine monophosphate dehydrogenase (IMPDH), inhibition of RNA‐dependent RNA polymerase (RdRp), and mutagenesis of viral replication (Fernandez et al ., ; Crotty et al ., ; Maag et al ., ).…”
Section: Introductionmentioning
confidence: 98%